Leaf-litter thrips of the genus Adraneothrips from Asia and Australia (Thysanoptera, Phlaeothripinae) - Dang, Li-Hong; Mound, Laurence A. (Zootaxa, 2013)
The Oriental genus Stigmothrips Ananthakrishnan is synonymised with Adraneothrips Hood, a genus in which most species have been described from the Neotropics. Problems with descriptions by T.N. Ananthakrishnan of species from India are discussed, but cannot be fully resolved without access to the holotypes. A key is provided to 23 species of Adraneothrips from Asia and Australia, including four new species: darwini sp. n. from Northern Territory, Australia; hani sp. n. from Taiwan, China; yunnanensis sp. n. from Yunnan, China as well as Java, Indonesia; and waui sp. n. from Papua New Guinea. One species from the Philippines, Adraneothrips makilingensis (Reyes) comb. n., is transferred from Apelaunothrips, and the male of Adraneothrips russatus (Haga) is described and illustrated for the first time, from Yunnan, China. Two species are newly recorded from Australia: coloratus (Mound) previously known only from the Solomon Islands, and russatus (Haga) previously known from southern Japan and southern China but with one female recorded here from Fiji. Further new records are, coloratus from Java, and chinensis (Zhang & Tong) from Malaysia. Colonies of species in this genus are commonly found living on dead leaves, as fungus-feeders, and many species are brightly coloured or bicoloured in patterns of yellow and brown.